Green Approaches and Sustainable Development of Conventional Methods of Bleaching Used in Paper Industry - Bhatnagar, Anju (Indian Forester, 2016)
The objective of the green approaches is to reduce chemical related impact on human health and eliminate contamination of the environment through fully and partially modified the conventional trends used in the bleaching of the pulp. The paper industry has always been associated with the various environmental issues. The pressure on paper industry is more due to discharge of chlorinated organic matter from bleach plant. In conventional bleaching chlorination/alkali extraction/hypochlorite/hypochlorite sequence is generally adopted. The main source of pollutants in chlorination and alkali extraction. The pollutant contribute for Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Toxic Chlorinated Compounds (TOX) and colour. During bleaching of the residual lignin of pulp generate the large amount organic chlorinated compounds in the effluent. The amount of chlorinated compound used for the bleaching of pulp is directly proportional of residual lignin of the pulp. The present study is partially replacement of the elemental chlorine by oxygen or fully replacement of the elemental chlorine by chlorine dioxide and peroxide. Effluent loads from different traditional and emerging ECF bleaching sequences were investigated. Oxygen delignified Eucalyptus tereticornis kraft pulps having similar kappa number 44.91 and 26.46 were used in this study. Different ECF bleaching sequences were compared with reference sequence, C/E/H/H O/C/E/H, O/C/E/H and O/C/E/P in terms of effluent load, such as COD, BOD and AOX. Depending on the nature of sequences 5 50.0% elemental chlorine consumption was reduced and as a result the amount of AOX formation was also reduced.